One‐Pot, Atom and Step Economy (PASE) Assembly of Trifluoromethylated Pyrimidines from CF3‐Ynones. Issue 28 (27th July 2017) - Romanov, Alexey R.; Rulev, Alexander Yu.; Ushakov, Igor A.; Muzalevskiy, Vasiliy M.; Nenajdenko, Valentine G.
Abstract : A highly efficient synthetic method for the preparation of of 6‐trifluoromethylated pyrimidines was developed. The reaction of CF3 ‐substituted ynones and nitrogen 1, 3‐bis(nucleophile)s was employed for the one‐pot assembly of the pyrimidine core. The cascade route proceeded through an aza‐Michael addition, intramolecular cyclization, and dehydration reaction sequence to give the target heterocycles in excellent yields (up to 97 %). When acetamidine was used as the bis(nucleophile), the unexpected addition of two equivalents of the CF3 ‐substituted ynone to the acetamidine was observed. Abstract : Trifluoromethyl‐substituted ynones are shown to be convenient building blocks for the preparation of fluorinated pyrimidines. The one‐pot, atom and step economy (PASE) method towards trifluoromethylated pyrimidines proved to be efficient, simple, and applicable towards a variety of acetylenic ketones and 1, 3‐bis(nucleophile)s.